2023
DOI: 10.3390/ijms24043135
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Promising Drug Candidates against Prostate Cancer through Computationally-Driven Drug Repurposing

Abstract: Prostate cancer (PC) is one of the most common types of cancer in males. Although early stages of PC are generally associated with favorable outcomes, advanced phases of the disease present a significantly poorer prognosis. Moreover, currently available therapeutic options for the treatment of PC are still limited, being mainly focused on androgen deprivation therapies and being characterized by low efficacy in patients. As a consequence, there is a pressing need to identify alternative and more effective ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 189 publications
1
1
0
Order By: Relevance
“…Similar considerations arise from the study of Bernal et al [15], in which different types of ligand-based similarity estimations were performed between molecules with reported antiproliferative activity against prostate cancer (PC) cells and DrugBank compounds [16]. In this study, the performed analyses were also integrated with target-related activity data reported for PC, allowing the authors to identify 48 DrugBank compounds as potential repurposing or repositioning candidates, 5 of which have already been studied in clinical trials for prostate cancer.…”
supporting
confidence: 57%
“…Similar considerations arise from the study of Bernal et al [15], in which different types of ligand-based similarity estimations were performed between molecules with reported antiproliferative activity against prostate cancer (PC) cells and DrugBank compounds [16]. In this study, the performed analyses were also integrated with target-related activity data reported for PC, allowing the authors to identify 48 DrugBank compounds as potential repurposing or repositioning candidates, 5 of which have already been studied in clinical trials for prostate cancer.…”
supporting
confidence: 57%
“…The primary factors examined in docking investigations encompassed binding energy [20], hydrogen bonding [21], hydrophobic interaction [22], and electrostatic interaction [23]. The results of this investigation provide valuable insights into the potential effectiveness and speci city of these derivatives, thereby offering guidance for subsequent experimental efforts in the realm of pharmaceutical development [24].…”
Section: Introductionmentioning
confidence: 99%